A Comparative Analysis of Government Social Spending Indicators and Their Correlation with Social Outcomes in Sub-Saharan Africa - Lopes, Paulo (IMF Working Papers; Working Paper ;, 2002)
This paper analyzes trends in social indicators in sub-Saharan Africa (SSA) and their correlation with the three most widely used scaled measures of government social spending: in per capita terms, as a percentage of GDP, and as a percentage of total government expenditure. On the basis of a regional data set matching health and education outcome indicators with government spending on those sectors, cross-country statistical analysis shows spending both per capita and as a percent of GDP to be of some relevance to social outcomes, but not the share of social spending in budgetary allocations. The policy implications concern not only governments in the region, but also the international donor community for its role in supporting social programs in SSA.